Conventional Dissection and Bipolar Electrocauterization Methods of Tonsillectomy: A Comparative Study - Sharma, Anshu; Bhandari, Shama; Paudel, Dhundi Raj (Journal of Nepalgunj Medical College, 2022)
Introduction: Tonsillectomy is frequently performed surgical procedure. There are several different methods with varied advantages and disadvantages. In spite of the different techniques available there is no consensus and definite evidence for best method. The most commonly performed are conventional dissection and bipolar electrocauterization methods.Aims: The aim of the study was to compare time required for the completion of surgery, intraoperative and postoperative blood loss along with post operative pain between conventional dissection and bipolar electrocauterization methods.Methods: This comparative study was conducted from August 2019 to March 2021 in total of 30 patients planned for tonsillectomy in department of Otorhinolaryngology, Nepalgunj Medical College Teaching Hospital.In every patient right side tonsillectomy was done with conventional dissection method and left side tonsillectomy was done with bipolar electrocauterization method.Results: The mean age was 27.2±13.08 years. The mean duration of surgery was 16.53 ± 2.43 min and 11.10 ± 1.93 min in conventional dissection method and bipolar electrocauterization method respectively. The difference was statistically significant. Intraoperative blood loss was significantly lower in bipolar electrocauterization method with mean intraoperative blood loss of 19 ±4.62 ml in bipolar electrocauterization group and 81.83 ±36.54 ml in conventional dissection method. The pain intensity was statistically similar in both methods at all-time intervals post operatively.Conclusion: In tonsillectomy, bipolar electrocauterization method has advantage over conventional dissection method in regards to reduced surgical time and intra operative blood loss, without any significant difference in post-operative pain intensity and post-operative hemorrhage.